SELF-ASSESSMENT TOOL FOR IMPROVING STUDENT’S SKILLS REGARDING THE EXAMS IN HIGHER EDUCATION - Shilan A. Mohammed; Nawzat S. Ahmed (Science Journal of University of Zakho, 2023)
Preparing for exams in higher education can be challenging, and students often need help to assess their skills and competencies. This paper presents a self-assessment tool to improve students’ exam preparation and performance. The study involved collecting data from students before and after using the tool, which asked questions related to exam preparation strategies such as understanding the exam format, imagining potential test questions, and following directions carefully. The results were compared to assess the tool's effectiveness in improving students' exam skills. The findings showed a significant improvement in the student’s self-assessment and exam performance after using the tool. This paper provides an overview and comparison of existing e-learning management systems and self-assessment tools to highlight the unique features of the proposed tool. The self-assessment tool was designed and tested, with a pre-feedback and post-feedback evaluation of students' skills. Comparing pre and post results showed a statistically significant improvement in students' skills, leading to a notable shift in the percentage of responses. The "never" category experienced a considerable decrease of 27.91%, while the "always" category witnessed a substantial increase of 53.46%. These findings underscore the positive impact of the self-assessment tool on students' behaviors and attitudes toward exam preparation. Overall, this study showcases how self-assessment tools can effectively improve test readiness and outcomes in higher education.